Multi-Omics Analysis of Mammary Metabolic Changes in Dairy Cows Exposed to Hypoxia - Kong, Zhiwei; Li, Bin; Zhou, Chuanshe; He, Qinghua; Zheng, Yuzhong; Tan, Zhiliang (Frontiers in Veterinary Science, 2021)
Hypoxia response is a complex process involving various physiological and biochemical changes. Our previous studies found the milk fat rate increased significantly in hypoxic dairy cows, however, its specific metabolic mechanism is unclear. In this experiment, we explored and verified the mechanism of hypoxia adaptation based on the apparent and omics results of animal experiments and in vitro cell model. The results revealed that hypoxia exposure was associated with the elevation of AGPAT2-mediated glycerophospholipid metabolism. These intracellular metabolic disorders consequently led to the lipid disturbances related to cell apoptosis. Our findings update the existing understanding of increased adaptability of dairy cows exposure to hypoxia at the metabolic level.